Integrating expressive arts and play therapy with children and adolescents - Green, Eric J.; Drewes, Athena A. 1948- (Hoboken, New Jersey Wiley, 2014)
"Clinicians certified in the expressive art therapies--the visual arts, movement, drama, music, writing and other creative processes--are typically unfamiliar with some of the interventions and approaches used in play therapy. This book bridges the divide between play therapy and expressive arts therapy, so that therapists in each field can integrate evidence-informed practices from both expressive arts and play therapy into their practice with children and adolescents. Play therapists as well as those who specialize in expressive arts therapies, as well as mental health professionals looking to integrate both into their practice will benefit from this book's exposure to the diverse and innovative approaches within the expressive arts and play therapy literature"--Provided by publisher.
1. The expressive arts therapy continuum: history and theory / Sandra L. Graves-Alcorn and Eric J. Green -- 2. Play therapy / Athena A. Drewes and Sue C. Bratton -- 3. Art therapy / Reina Lombardi --4. Drama therapy / Eleanor Irwin -- 5. Integrating play therapy and sandplay therapy / Rie Rogers Mitchell, Harriet S. Friedman, and Eric J. Green -- 6. Working with children using dance/movement therapy / Mariah Meyer LeFeber -- 7. Music therapy / Susan Hadley and Nicole Steele -- 8. The therapeutic uses of photography in play therapy / Robert Irwin Wolf -- 9. Poetry therapy / Diane L. Kaufman, Rebecca C. Chalmers, and Wendy Rosenberg -- 10. Integrating play and expressive art therapy into educational settings: a pedagogy for optimistic therapists / Jodi M. Crane and Jennifer N. Baggerly -- 11. Integrating play and expressive art therapy into small group counseling with preadolescents: a humanistic approach / Sue C. Bratton, Dalena Dillman Taylor, and Sinem Akay -- 12. Integrating play and expressive art therapy into communities: a multimodal approach / Julia Byers.
Includes bibliographical references and index.
Keywords: Arts -- Therapeutic use; Play therapy; Performing arts -- Therapeutic use; Psychotherapy -- Practice